Water painting technology and its aesthetic values (Damascus University Journal for engineering sciences, 2024)
This article illuminates the water imaging technique and its importance in the construction of art paintings, it is one of the important techniques in the art of painting and photography with aesthetic, formative values and unique characteristics The article aims to recognize the technical hedge ,its history and its distinctive characteristics ,as well as the materials needed for and its style ,finally address some of the international ,Arab and Syrian forms to show how to deal with this technique and to.
Keywords: Technique; Imaging; Water; Values; Aesthetic; Emotion; Poetics; Romance